Oxidation leaching of chromium from electroplating sludge: Ultrasonic enhancement and its mechanism - Huang, Kaihua; Wang, Lizhangzheng; Wen, Yong; He, Kuang; Zhang, Mingyang; Du, Jianwei; Hu, Xiaoying (Frontiers in Chemistry, 2022)
The oxidation leaching of chromium from electroplating sludge was investigated and ultrasonic was introduced for the enhancement of the leaching process. Two different types of Cr-bearing electroplating sludge were selected for the study and the effect of reagent dosage, temperature and ultrasonic pulse ratio on the leaching efficiency were tested through oxidation leaching experiments. The experimental results show that hydrogen peroxide and sodium hypochlorite exhibit different leaching effects on different types of electroplating sludge. The control of reagent dosage is crucial for the oxidation leaching of Cr while the effect of temperature turns out to be small. Hydrogen peroxide turns out to be a more effective oxidizer for chromium sludge, and the leaching efficiency of Cr could be promoted from 77.52% to 87.08% by ultrasonic under optimum conditions. Interestingly, Sodium hypochlorite exhibited better leaching efficiency than hydrogen peroxide for the mixed sludge, since the organic matter in the mixed sludge will lead to the rapid decomposition and consumption of hydrogen peroxide. The leaching efficiency of Cr from the mixed sludge could also be promoted from 56.82% to 67.10% by ultrasonic under optimum conditions. According to the scanning electron microscope imaging, ultrasonic can create voids and cracks on the surface of the sludge particles, hence promote the contact between electroplating sludge and leaching agents and promote the oxidation leaching efficiency. In addition, ultrasound seems to be able to remove the coverings on the surface of the mixed sludge particles, which may facilitate the oxidation reaction.